Careers in dance: beyond performance to the real world of work - Bennett, Dawn (J. Michael Ryan Publishing, Inc., 2009)
For the majority of undergraduate dance students, success is the realization of a career in performance; however, given that this will be the outcome for so few graduates, should this ideal be redefined? This paper draws on findings from a case study of Australian dance artists, which sought to determine how dance artists allocate their working time and what skills they utilise to sustain their careers. Results reveal the multiplicity and diversity of roles in which Australian dance artists engage, and a corresponding need to include career development, self-management and small business skills within pre-professional dance performance programs.